ANALISIS KEBIJAKAN PEMERINTAH DALAM PELAYANAN KEPELABUHAN DAN KESELAMATAN LINGKUNGAN PELAYARAN PADA TERMINAL PETI KEMAS PALARAN SAMARINDA - Esti Royani; Dody Hasrizal Siahaan (The Juris, 2022)
One of the product and services that play an important role in the port services and shipping safety. Port services is very important because the service is not only about security, but even more a problem of life safety for users of transport services or shipping. Shipping in terms of working time and discipline is the arrangements relating to the problems of the transport. The transport of goods and passengers both in accordance with international conventions in the field of shipping. Shipping safety is a requirement that must be met in the transport in the sea, harbor and maritime environment. Where the ship as a means of transport at the sea must be able to following the safety requirements, prevention of the sea pollution, manning, load line, stowage, the welfare of the crew and passenger health and legal status.Thus the policy of the Government in the service of port and shipping environmental safety must be undertaken in accordance with the guidelines supported by loyalty in encouraging the desired results either by the Government itself as a regulator or for the service users and the public.In addition to policy issues concerning safety and security of shipping as a public service institution, course the quality of service to the parties concerned, especially in the field of port services which affect the safety of shipping.